PENERAPAN PEMBELAJARAN BERBASIS DIGITAL DI MTs NEGERI 1 PALU - Arnela Nur Airilya Putri; Sitti Nuralan; Saugadi (Jurnal Teknologi Pendidikan Madako, 2025)
This study aims to identify and describe the implementation of digital based learning at MTs Negeri 1 Palu, focusing on its strategies, shortcomings, and effectiveness. This study uses a qualitative approach with a case study method. Data collection techniques were carried out through observation, interviews, and documentation. The subjects of the study consisted of 5 students, 1 subject teacher, and 1 digital class coordinator. The results of the study indicate that digital learning at MTs Negeri 1 Palu involves madrasah policies, the provision of infrastructure and teacher capacity, the utilization of E-learning platforms, and digitally integrated methods for content delivery and assignments. Shortcomings in the implementation of digital learning at MTs Negeri 1 Palu are primarily related to network issues, device limitations, and a lack of mastery of basic applications. Digital learning effectively enhances student understanding and comfort through interactivity and accessibility. Teachers also experienced administrative efficiency. However, this effectiveness varies due to digital distractions as well as students diverse preferences and competencies. This study recommends improvements in infrastructure, digital literacy, and further comparative studies.